2023
DOI: 10.1039/d3lc00398a
|View full text |Cite
|
Sign up to set email alerts
|

Label-free virtual staining of neutrophil extracellular traps (NETs) in microfluidics

Abstract: Neutrophils are the most abundant circulating white blood cells and one of their critical functions to eliminate pathogenic threats includes the release of extracellular DNA, also known as neutrophil extracellular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Aside from the visualization of the cell-cell interaction, another important advantage of these assays is the ability to study neutrophil behavior and functions in real-time. For example, studies have shown that when using biomimetic microfluidic assays, neutrophil migration ( Boribong et al., 2019 ) and NETosis ( Petchakup et al., 2023 ) can be observed. Furthermore, biomimetic microfluidic assays can be used to observe the process of neutrophils eliminating pathogens such as fungal clusters ( Alex et al., 2020 ) and bacteria ( Ellett et al., 2019 ) in real-time.…”
Section: Emerging In Vitro Models – the Promise Of...mentioning
confidence: 99%
“…Aside from the visualization of the cell-cell interaction, another important advantage of these assays is the ability to study neutrophil behavior and functions in real-time. For example, studies have shown that when using biomimetic microfluidic assays, neutrophil migration ( Boribong et al., 2019 ) and NETosis ( Petchakup et al., 2023 ) can be observed. Furthermore, biomimetic microfluidic assays can be used to observe the process of neutrophils eliminating pathogens such as fungal clusters ( Alex et al., 2020 ) and bacteria ( Ellett et al., 2019 ) in real-time.…”
Section: Emerging In Vitro Models – the Promise Of...mentioning
confidence: 99%